Excessive physical activity increased leucocyte and decreased Endorphin levels in male wistar rats (Rattus norvegicus) - Periskila Abigail; Wimpie Pangkahila; Alex Pangkahila (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2021)
Background: Excessive physical activity triggers hormonal imbalances, one of which is beta endorphin and lead to increasing leukocytes as a response to the inflammation. The purpose of this study was to prove that excessive physical activity increased leucocyte and decreased endorphin levels in male Wistar rats (Rattus norvegicus). Methods: This study was an experimental study with randomized pretest-posttest group design. The research subjects were male rats (Rattus norvegicus), Wistar strain, aged 8-10 weeks with a body weight of 150-200 grams and healthy. A total of 14 rats were randomly divided into two groups. The first group was treated with balanced physical activity (P1), the second group was treated with excessive physical activity (P2). On day 8 and day 28, leukocytes were examined using whole blood method and beta endorphin were examined using ELISA. Results: The results showed that in the group P1, both leukocyte levels (from 14.0±2.73x103/µL to 17.1±5.07x103/µL, p= 0.170) and beta endorphin levels (from 176±30.2 to 161±11.1 ng/mL, p= 0.110) remained stable. Whereas, the P2 group experienced leukocyte reduction (from 12.3±2.19x103/µL to 23.7±2.92x103/µL, p <0.001) and decreased beta endorphin levels (from 212±46.0 ng/mL to 55.3±8.05 ng/mL, p <0.001). Conclusion: This study suggesting that excessive physical activity increased leucocyte and decreased endorphin levels in male Wistar rats (Rattus norvegicus).